Cover Picture: Stereo‐ and Regioselective Phyllobilane Oxidation in Leaf Homogenates of the Peace Lily (Spathiphyllum wallisii): Hypothetical Endogenous Path to Yellow Chlorophyll Catabolites (Chem. Eur. J. 1/2015). Issue 1 (2nd January 2015) - Vergeiner, Clemens; Ulrich, Markus; Li, Chengjie; Liu, Xiujun; Müller, Thomas; Kräutler, Bernhard
<x xml:space="preserve">Abstract</x> Chlorophyll is broken down in leaves during Fall to colorless tetrapyrroles, so‐called phyllobilanes, which are degraded further in leaves into yellow oxidation products. The hypothetical "missing link" between the colorless and the yellow catabolites has now appeared on the scene, as described in the Full Paper by B. Kräutler et al. on page 136 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>